Multivergensie: ’n Netwerk van ekwivalensieverhoudinge - Trautmann, Christelle (Lexikos, 1994)
Multivergence: A Network of Equivalence Relations In a translation dictionary source language items are represented as lemmas and translation equivalents are provided for the source language items. Due to this lexicographical practice different types of equivalence relations exist between the source items and the target language items. Multivergence is a type of equivalence relation that has a high frequency in translation dictionaries. This is caused by the semantic structure of languages. The general perception is that multivergence is a combination of two equivalence relations, namely divergence and convergence. Owing to this definition of multivergence, an explanation of divergence and convergence is required. In this study reference is made to lexical and semantic divergence and convergence. Different types of multivergence are distinguished: (i) lexical divergence and lexical convergence (ii) lexical divergence and semantic convergence (iii) semantic divergence and lexical convergence (iv) semantic divergence and semantic convergence Attention is also given to communicative equivalence as well as the synonymity that exists between lexical items. Intra- and interlingual semantic relations are discussed. The practical lexicographer, who has knowledge about these relations, will focus the attention of the dictionary user on the target language items that can be used as translation equivalents of a lemma. It is a user-friendly representation of equivalents that simplifies the equivalent choice made by the user. If convergence is illustrated by means of a reference, the user will conclude from this practice which lemmas are semantically related and can be coordinated with a single equivalent. The study further stresses the importance of a complete representation of lexical items. Such a practice acknowledges the existence of a network of equivalence relations. Keywords: communicative equivalence, connotation, denotation, dictionary, equivalence relation, lexical convergence, lexical divergence, lexicographer, multivergence, paradigm of target language items, semantic convergence, semantic divergence, source language item, synonymity, target language item